An investigation on the key features of a D–π–A type novel chalcone derivative for opto-electronic applications. Issue 106 (15th October 2015) - Shkir, Mohd.; Muhammad, Shabbir; AlFaify, Salem; Irfan, Ahmad; Patil, Parutagouda Shankaragouda; Arora, Manju; Algarni, Hamed; Jingping, Zhang
Abstract : The calculated UV-visible optical spectra at different levels of theory. Abstract : The current study is focused on the donor–bridge–acceptor (D–π–A) type of novel organic charge transport and non-linear optical material, 1-(4-bromophenyl)-3-(2, 4, 5-trimethoxyphenyl) prop-2-en-1-one (2, 4, 5-TMBC) to spotlight its various important properties through experimental and quantum chemical approaches. The compound 2, 4, 5-TMBC was synthesized via a Claisen–Schmidt condensation reaction and its single crystal was grown by a slow evaporation solution growth technique. FT-IR and FT-Raman spectra of 2, 4, 5-TMBC were obtained and investigated. The molecular geometry of 2, 4, 5-TMBC was optimized by HF, B3LYP, CAM-B3LYP, wb97xd and LC-BLYP methods using the 6-31G* basis set. The calculated geometrical parameters and vibrational spectra are in good agreement with the experimental results. Time dependent density functional theory (TD-DFT) has been applied to investigate the optical properties of the title compound. The absorption wavelength calculated at the TD-B3LYP/6-31G* level of theory in the gas phase was in good agreement with the experimental value (∼400 nm) when compared with other methods. The HOMO–LUMO energy gap was calculated at all the applied levels of theory. The total dipole moment, polarizability, anisotropy of polarizability and static first and total hyperpolarizability values of 2, 4, 5-TMBC were calculated at different levels of theory. The dipole moment and first hyperpolarizability values are found to be many folds (2 and 56 times calculated at B3LYP) higher than urea. It is also expected that 2, 4, 5-TMBC would be electron transport material due to its smaller electron reorganization energy value. The study of non-linear optical (NLO) properties shows that 2, 4, 5-TMBC would be an outstanding candidate for NLO device applications.